Development of the TALUBA Model to Increase Science, Islam, and Local Wisdom and Instill Taluba Character - Lutfiyanti Fitriah; Agil Karwi Wadila Vanianingrum; Agil Karwi Wadila Vanianingrum; Rini Wulan Sari; Rini Wulan Sari; Risda Rokhmania Nur Hikma; Risda Rokhmania Nur Hikma; Fahmi Yahya; Fahmi Yahya (Universitas Lambung Mangkurat, 2024)
This research aimed to create TALUBA learning model-assisted modules that enhance three different forms of literacy. These were the literacy of science, Islam, and indigenous wisdom. The other was to maintain honorable character. The South Kalimantan people's local characters, especially Baiman (faithful), Bauntung (fortunate), and Batuah (dignified), are known as the taluba (three ‘ba’) characters. Using the ADDIE design, this study was a research and development project. Twenty-eight students studying work and energy in Basic Physics served as the research sample. The study instruments were the validation sheets, observation sheets, test questions, and questionnaires. Tests, observations, and surveys were the methods utilized to acquire data. The Aiken formula, N-Gain, mean, and percentage were employed in the data analysis. With a value of 0.92-1.00, learning models and modules were known to be valid based on the data analysis results. In the very good category, the average application of the learning model by lecturers was 4.85, while for students, it was 4.30. According to the test findings, the N-gains for literacy in scientific, Islamic, and local wisdom were 0.93, 0.92, and 0.94 in the high group, respectively. The very good category's average taluba character was 4.61. Additionally, there was a good reaction from students to the learning models and modules. This suggests that the proposed TALUBA learning model is appropriate for lecture use.